Synergy of botanical drug extracts from Dracaena cochinchinensis stemwood and Ardisia elliptica fruit in multifunctional effects on neuroprotection and anti-inflammation - Ospondpant, Dusadee; Lai, Queenie Wing Sze; Dong, Tina Tingxia; Tsim, Karl Wah Keung (Frontiers in Pharmacology, 2024)
Combination therapy is one of the promising approaches in developing therapeutics to cure complex diseases, such as Alzheimer’s disease (AD). In Thai traditional medicines, the clinical application often comprises multiple botanical drugs as a formulation. The synergistic interactions between botanical drugs in combination therapies are proposed to have several advantages, including increased therapeutic efficacy, and decreased toxicity and/or adverse effects. This study aimed to explore the therapeutic functions of a botanical hybrid preparation (BHP) of two botanical drugs within a traditional multi-herbal formulation. The synergistic actions of BHP of Dracaena cochinchinensis stemwood (DCS) and Ardisia elliptica fruit (AEF) at a specific ratio of 1:9 w/w were illustrated in neuroprotection and anti-inflammation. In cultured PC12 cells, BHP of DCS and AEF showed synergistic functions in inducing neuronal differentiation, characterized by neurofilament expression and neurite outgrowth. In addition, BHP of DCS and AEF exhibited a synergistic effect in inhibiting the aggregation of Aβ, a hallmark of AD pathology. The activated BV2 microglial cells induced by LPS were synergistically suppressed by the BHP of DCS and AEF, as evaluated by the expression of pro-inflammatory markers, including TNF-α, IL-1β, and iNOS, as well as the morphological change of microglial cells. The findings suggested that the effects of BHP of DCS and AEF were greater than individual botanical drugs in a specific ratio of 1:9 w/w to enhance neuroprotective and anti-inflammatory functions.